Effect of Long-term Azithromycin in Reducing Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Saleem, Husnain; Amir, Muhammad; Gardezi, Syed Anees Ahmed; Amir, Mumtaz; Zulqarnain; Saleem, Hasan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the effect of long-term Azithromycin administration in reducing acute exacerbation of Chronic Obstructive Pulmonary Diseases. Study Design: Quasi-experimental study. Place and Duration of Study: Medicine and Pulmonology Departments of Combined Military Hospital, Peshawar Pakistan, from Jun 2019 to May 2020. Methodology: Patients of Chronic Obstructive Pulmonary Diseases who had more than three hospital admissions in the last one year or required parenteral steroids for management were included in the study. They were randomly divided into two groups where Group-I was administered Azithromycin 500mg, thrice weekly, in addition to routine Chronic Obstructive Pulmonary Diseases medications, and Group-2 received only routine Chronic Obstructive Pulmonary Diseases medications. Both groups were compared for hospital admission due to Chronic Obstructive Pulmonary Diseases, hospital admission due to other causes, parenteral steroid use and Emergency Department visits after six months. Results: Out of 150 patients of Chronic Obstructive Pulmonary Diseases, 78(52%) received Azithromycin for six months while 72(48%) received only usual treatment of Chronic Obstructive Pulmonary Diseases, while 13(16.6%) patients from Azithromycin-Group had more than three Chronic Obstructive Pulmonary Disease related hospital admissions in six months. However, 34(47.2%) patients in non-Azithromycin-Group had more than three such admissions. More than three Chronic Obstructive Pulmonary Disease related hospital admissions and use of parenteral steroids were found significantly more in non-Azithromycin-Group (p-value <0.001). Conclusion: Long-term Azithromycin use was found beneficial for patients suffering from Chronic Obstructive Pulmonary Diseases. Use of parenteral steroids and Chronic Obstructive Pulmonary.....